Group Performance of Tribal FIGs in Erode District of Tamil Nadu: A Case of Belauri Municipality - V. Mathuabirami; S. Kalaivani (Journal of Agricultural Extension Management, 2022)
Small and marginal tribal farmers are facing the problem of a poor marketing system and lack of quality input and technical services. This problem can be addressed through group approaches like Farmer Producer Organization (FPO), Farmers Interest Group (FIG) and Self Help Group (SHG). Farmers Interest Group (FIG) is a self managed, independent group of farmers with a shared goal and interest. FIG is usually formed by 15 - 20 members. When the farmers are facilitated to organize groups, trained and guided properly, they can attain tremendous development goals which would eventually make the group self- reliant and self sufficient. This paper attempts to study the performance of Tribal FIGs which were formed by MYRADA KVK, to understand the functioning of FIGs. The study reveals that majority of the members of Tribal FIGs reported that the FIG had a medium level of group performance.